2000
DOI: 10.1021/jp000820y
|View full text |Cite
|
Sign up to set email alerts
|

Periodic Density Functional LDA and GGA Study of CO Adsorption at the (001) Surface of MgO

Abstract: The deficiencies of the local density approximation (LDA) to describe weakly adsorbed species on ionic surfaces are exposed in the current study of CO on the (001) surface of MgO. We applied a periodic formulation of density functional theory with crystal orbitals and charge density expanded as linear combinations of atomic orbitals of Gaussian form. The binding was investigated for four orientations of the CO molecule:  either the carbon or oxygen atom of CO down over either the surface magnesium cation or ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 50 publications
(121 reference statements)
3
20
1
Order By: Relevance
“…Similarly, for the change in the CO vibrational frequency due to the adsorption, similar calculations have been performed in Refs. [25,27,40,41]. Our results match the other results, when available, quite well.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Similarly, for the change in the CO vibrational frequency due to the adsorption, similar calculations have been performed in Refs. [25,27,40,41]. Our results match the other results, when available, quite well.…”
Section: Resultssupporting
confidence: 90%
“…[40] reports an adsorption energy of 0.02 eV, Ref. [41] 0.08 eV, and Ref. [42] reports values between 0.0 and 0.48 eV depending on the calculation method, with 0.07 eV considered the most accurate result by the authors of Ref.…”
Section: Resultsmentioning
confidence: 99%
“…Both CO and NO are used as common probe molecules in surface science to obtain fundamental information about the gas-surface interactions, adsorption sites, and reactive dynamics on a variety of metals [1][2][3][4][5][6], semiconductors [7][8][9][10][11], and insulator surfaces. Moreever, CO and NO are both one of the most hazardous products released by car exhausts.…”
Section: Introductionmentioning
confidence: 99%
“…DFT (density functional theory) methods have begun its venture in oxides somewhat later but progressed in a rapid manner; hence, a number of studies have been reported in the last decade on oxides as well as other materials [18][19][20][21][22][23][24][25]. In the last couple of years, there have been considerable progresses in the area [26][27][28][29][30][31][32] of electronic and structural properties of mixed metal oxides using first principle density functional theory.…”
Section: Introductionmentioning
confidence: 99%